The Danger Signs in Pregnancy in Pregnant Women in the UPT area of the Ulaweng Public Health Center, Ulaweng District, Bone Regency in 2022 - Andi Ria Metasari; Sumarni; Kasmiati; Susilawati; Sriwidyastuti (PT Inovasi Pratama Internasional, 2022)
75% of maternal deaths are caused by bleeding, infection, and high blood pressure in the mother during pregnancy. Danger signs in pregnancy are a sign that a serious problem has occurred in the pregnant mother or the fetus in her womb so that it can cause illness or death before or after delivery. The method of this community service is the extension method in the form of direct presentation of lecture material to 20 pregnant women using leaflets and browsur media. This community service as a whole is very effective, so that an increase in knowledge is obtained after counseling on the danger signs of pregnancy to pregnant women